Pengembangan E-Modul Pembelajaran Statistika Kelas VIII SMP Berbasis Worked Example - Fahira Muzdhalifah Lukum; Perry Zakaria; Auli Irfah (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to develop a Worked Example-based statistics e-module for Grade VIII junior high school students. The development is motivated by the need for digital teaching materials that can enhance students’ understanding of statistical concepts in a gradual and systematic manner through structured problem-solving examples. This research employed the Research and Development (R&D) method using the 4D development model, which consists of Define, Design, Develop, and Disseminate stages. The Define stage involved needs analysis, student characteristics analysis, and content analysis. The Design stage focused on constructing the structure of the Worked Example-based e-module. The Develop stage included validation by media and subject matter experts, as well as practicality testing through readability tests, student response questionnaires, and teacher responses. The Disseminate stage was conducted on a limited scale to evaluate the feasibility of the product in instructional settings. The results indicated that the developed e-module met both validity and practicality criteria. Media validation obtained an average score of 3.45, categorized as highly valid, while material validation achieved an average score of 3.17, categorized as valid. The readability test resulted in a percentage of 90.87%, categorized as highly positive. Student responses reached 88.54%, also categorized as highly positive, while teacher responses attained 97.22%, categorized as highly practical. Based on these findings, it can be concluded that the Worked Example-based statistics e-module is feasible and effective as a learning medium for Grade VIII junior high school students.